Electrochemical determination of lead and glutathione in a plant cell culture - Vacek, Jan; Petrek, Jirí; Kizek, René; Havel, Ladislav; Klejdus, Borivoj; Trnková, Libuse; Jelen, Frantisek (Bioelectrochemistry (Amsterdam, Netherlands), 2004)
In this work we established differential pulse anodic stripping voltammetry (DPASV) as the tool for analysis of lead in the plant cell culture. For the cultivation procedure, lead in Pb(II)-ethylenediaminetetraacetic acid (Pb-EDTA) chelate has been used. The detection limit of lead was found at 500 pM in phosphate buffer (pH 5.5), and 100 nM in prepared cells intracellular extract (20 pg Pb(II)/mg cells). For determination of cysteine-rich peptides, voltammetry in differential mode (DPV) in cobalt(III)-containing ammonia buffer (Brdicka reaction) was used. In this short communication, we present suitable voltammetric techniques for the physiological study of lead and thiols in plant cell culture.
Keywords: Lead; Picea; Electrochemistry; buněčné kultury; Sulfhydryl Compounds; smrk; olovo; Cells, Cultured; koncentrace vodíkových iontů; sulfhydrylové sloučeniny; elektrochemie; Glutathione; Cell Culture Techniques; kultivované buňky; Hydrogen-Ion Concentration; glutathion